TiO2/SnOxCly double layer for highly efficient planar perovskite solar cells - Wu, Cuncun; Huang, Ziru; He, Yihao; Luo, Wei; Ting, Hungkit; Li, Tieyi; Sun, Weihai; Zhang, Qiaohui; Chen, Zhijian; Xiao, Lixin (ORGANIC ELECTRONICS, 2017)
Recently, perovskite solar cells have attracted tremendous research interest due to their amazing light to electric power conversion efficiency (PCE). However, most high performance devices usually use mesoporous TiO2 as the electron transport layer (ETL), which increases cost for practical application. Here, TiO2/SnOxCly double layer was employed as the ETL for planar perovskite solar cells. Compared with bare TiO2, perovskite solar cell based on TiO2/SnOxCly shows drastically improved power conversion efficiency and reduced hysteresis. These improvements are attributed to TiO2/SnOxCly which could enhance electron extraction and reduce surface trap-state. (C) 2017 Elsevier B.V. All rights reserved.